Creating basic professional competence of students in the process of teaching a foreign language - Natalia V. Ageenko; Alla A. Rybkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with new approaches to the implementation of the main objectives of foreign language teaching in non-language universities. Competence approach to learning in higher education creates conditions for mastering professional competences complex. The socio-cultural, communication, information, social and psychological competencies can be formed in the process of learning a foreign language in high school. Use of credible sources in the process of learning a foreign language is able to significantly improve the efficiency of the educational activities of teachers and create an atmosphere of real language communication. A significant role in this task plays the encyclopaedic approach, which refers to the expansion of the range of the studied material.